The City of the Dead as a place to live: unpacking the narratives about tomb communities - Logan, Lindsey Bertrand (Kansas State University, 2020)
The housing crisis in Cairo, Egypt is a “wicked problem” that has stumped planners and built environment professionals for decades. Cairo’s 20 million residents are engaged in an everyday struggle for space, particularly housing. The current housing stock does not respond to the residents’ everyday needs. Overpopulation and lack of affordable housing has resulted in residents squatting and self-building housing. My research centers around one such “informal” settlement called the City of the Dead (COD). A series of cemeteries located in Cairo’s city center, COD is home to many of Cairo’s poor and rural migrants. Planning efforts such as the Masterplan Cairo 2050 outline intentions to evict these residents, without details on their rehabilitation. Standing between decision makers and new or modified development, are embedded place narratives that cannot be erased. Narratives hold power to shape, change, and ignore what already exists. This thesis explores the narratives about the City of the Dead that are ignored in Masterplan Cairo 2050. Using qualitative methods, I focus on unpacking these narratives about COD, held by major stakeholders such as government officials, urban planners, popular media, and other sources, in order to elucidate how these, determine the negative planning outcomes proposed in policy documents. Based in the analysis of primary and supplementary data, I unpack the dominant narrative based in themes around legality, relocation, services, historical and cultural aspects, urban fabric, planning and governance. Through this in-depth analysis of themes and terminology used by respondents, I show that the dominant narrative about COD imagines it to be a cemetery and not a residential settlement. Also, evident in the plans and policies pertaining to COD, and in the terminology used to describe those who live in COD, this dominant narrative ignores the value that COD brings as a place to live to its residents.
Keywords: Informal settlement; City of the Dead; Greater Cairo Region; Narrative; Cemetery planning; Slums